Development and characterization of octreotide-modified curcumin plus docetaxel micelles for potential treatment of non-small-cell lung cancer. (21st October 2019) - An, Quan; Shi, Chen-Xiao; Guo, Hao; Xie, Shi-Min; Yang, Ying-Ying; Liu, Ying-Nan; Liu, Zi-Hao; Zhou, Chang-Zheng; Niu, Feng-Ju
Abstract: We prepared octreotide (OCT)-modified curcumin plus docetaxel micelles to enhance active targeting and inhibit tumor metastasis by destroying vasculogenic mimicry (VM) channels. Soluplus was applied as an amphiphilic material to form micelles via film dispersion. The cytotoxic effects, active cellular targeting, and inhibitory effects on metastasis were systematically evaluated in vitro using A549 cells, and in vivo antitumor effects were evaluated using xenograft tumor-bearing mice. In vitro assays indicated that the OCT-modified curcumin plus docetaxel micelles showed robust cytotoxicity on A549 cells and effectively inhibited VM channels and tumor metastasis. Studying the mechanism of action indicated that OCT-modified curcumin plus docetaxel micelles downregulated MMP-2 and HIF-1α. In vivo assays indicated that OCT-modified curcumin plus docetaxel micelles increased drug accumulation at tumor sites and showed obvious antitumor efficacy. The developed OCT-modified curcumin plus docetaxel micelles may offer a promising treatment strategy for non-small-cell lung cancer.